Revolutionizing dental research in the Pacific Islands: the Pacific Islands dental research framework - Lakshmikantha, Hemanth Tumkur; Gavidi, Ratu Osea; Leweni, Tokasa; Tiim, Kantara; Khan, Kaitlyn; Kumar, Samantha (Frontiers in Oral Health, 2025)
Traditional dental research paradigms often lack relevance in marginalized cultural contexts due to inherent biases and misalignment with local values. For Pacific Islanders, this issue is pronounced, as they face serious oral health challenges while remaining underrepresented in scientific discourse. In response, the authors developed the Pacific Islands Dental Research Framework (PIDRF), a culturally informed, community-driven model that directly addresses these limitations in conventional Western approaches. PIDRF supports indigenous priority-setting, reciprocal co-gauging, and cross-sector collaboration throughout the research process, guided by cultural relationship specialists and indigenous advisory boards. This framework expands diagnostic assessments to incorporate cultural and social determinants of oral health, combining holistic and culturally tailored therapies. By continuously integrating patient feedback, PIDRF fosters empathetic, effective support that aligns with Pacific values. PIDRF promotes knowledge-sharing, policy reform, and community-led advancements, enabling Pacific communities to lead in improving their oral health outcomes. This framework introduces an ethical, decolonized model for dental research, setting a new standard for culturally responsive research in Pacific contexts.